2012
DOI: 10.1002/app.38074
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and dielectric relaxation spectroscopy of ternary polymer blends of polyamide6, polypropylene, and acrylonitrile butadiene styrene co‐polymer: Influence of compatibilizer and multiwall carbon nanotubes

Abstract: Morphological investigation was carried out with melt-mixed ternary polymer blends of polyamide6 (PA6), polypropylene (PP) and acrylonitrile butadiene styrene copolymer (ABS) in the presence of compatibilizer and multiwall carbon nanotubes (MWNTs). 80/10/10 (wt/wt/wt) PA6/PP/ABS and 80/10/10 (wt/wt/wt) PP/PA6/ABS blends exhibited ''core-shell'' morphology, whereas 80/10/10 (wt/wt/wt) ABS/PP/PA6 blends exhibited ''separately dispersed'' phase morphology. The type of phase morphology was unaltered in the presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
2
5
0
Order By: Relevance
“…Lower torque value for the blends with SMA + MWNTs as compared to the blend containing only SMA could originate from a lower extent of melt–interfacial reaction between PA6 and SMA copolymer in presence of MWNTs. A similar observation was also observed in 80/10/10 (wt/wt/wt) PA6/PP/ABS ternary polymer blends in presence of SMA copolymer and MWNTs . However, a minor fraction of MWNTs may even be wrapped with SMA copolymer, which may be trapped at the interface, since SMA copolymer may interact well with MWNTs.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…Lower torque value for the blends with SMA + MWNTs as compared to the blend containing only SMA could originate from a lower extent of melt–interfacial reaction between PA6 and SMA copolymer in presence of MWNTs. A similar observation was also observed in 80/10/10 (wt/wt/wt) PA6/PP/ABS ternary polymer blends in presence of SMA copolymer and MWNTs . However, a minor fraction of MWNTs may even be wrapped with SMA copolymer, which may be trapped at the interface, since SMA copolymer may interact well with MWNTs.…”
Section: Resultssupporting
confidence: 81%
“…Amide I and amide II peaks (∼1543 and ∼1642 cm −1 , respectively) can be observed from the plot which are the characteristic peaks for PA6 phase. The peaks at ∼1736 and ∼1776 cm −1 in presence of SMA copolymer confirms the imide bond formation due to the melt–interfacial reaction during melt‐mixing .…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…Thus, the refinement in the ‘co‐continuous’ structure of the blends can be explained due to compatibilizer‐like action of MWCNTs though MWCNTs did not change the interfacial behavior . Similar observations have been made in the case of binary blends of PP/ABS and ternary blends of PA6/PP/ABS, wherein the nanotubes selectively localized in one of the phases and altered the viscosity‐ratio and also prevented the rate of coalescence of the droplets by acting as a physical barrier between the droplets …”
Section: Resultssupporting
confidence: 64%
“…In another work, Panda et al . investigated the influence of MWCNTs addition on the phase morphology and electrical conductivity of PP/PA6/ABS ternary blends . They showed that incorporation of MWCNTs into ternary blends, generally, did not alter the type of phase morphology corresponding to respective blends.…”
Section: Introductionmentioning
confidence: 87%